2021
DOI: 10.1021/acsami.1c01992
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Lightweight Polyimide Honeycombs with the High Specific Strength and Temperature Resistance

Abstract: Lightweight structures are often used for applications requiring higher strength-to-weight ratios and lower densities, such as in aircraft, vehicles, and various engine components. Three-dimensional (3D) printing technology has been widely used for lightweight polymer structures because of the superior flexibility, personalized design, and ease of operation offered by it. However, synthesis of lightweight polymeric structures that possess both high specific strength and glass transfer temperature (T g ) remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Aromatic polyimide films have been widely used in many high-tech fields, including electrical insulation [ 15 , 16 , 17 , 18 , 19 , 20 ], electronic packaging [ 21 , 22 ], and aerospace [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], due to their excellent combination of thermal, mechanical, and electrical properties. Aromatic polyimide films can be made by casting the polyimide precursor solution–polyamic acid (PAA) on the substrate surface, and then thermally baking it to form a self-supporting gelled film.…”
Section: Aromatic Polyimide Filmsmentioning
confidence: 99%
“…Aromatic polyimide films have been widely used in many high-tech fields, including electrical insulation [ 15 , 16 , 17 , 18 , 19 , 20 ], electronic packaging [ 21 , 22 ], and aerospace [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], due to their excellent combination of thermal, mechanical, and electrical properties. Aromatic polyimide films can be made by casting the polyimide precursor solution–polyamic acid (PAA) on the substrate surface, and then thermally baking it to form a self-supporting gelled film.…”
Section: Aromatic Polyimide Filmsmentioning
confidence: 99%
“…Others focused their efforts on noncovalently crosslinked PI systems such as DIW‐printable water‐swellable PAAs (Fig. 7(b)) described by Chen and co‐workers 22 . PAA hydrogen bond disruption with triethylamine neutralization produced sufficient ink viscosities for DIW extrusion and ensuing material solidification post‐extrusion.…”
Section: Am Of Polyimidesmentioning
confidence: 99%
“…3D‐printed PIs: (a) FFF of PI thermosetting filament 21 ; (b) PI honeycomb printed from water with DIW 22 ; (c) UV‐assisted DIW of fully aromatic PI part 26 ; (d) carbonaceous structure formed from the carbonization of a PI part printed through a VP process 27 …”
Section: Am Of Polyimidesmentioning
confidence: 99%
“…Our results indicate that CNCs can be used as renewable fillers to 3D print PI/CNC composite aerogels with enhanced mechanical strength. Although our PAAS/CNC ink was printed under room temperature, several previous works preheated the inks to reduce the viscosity of the ink, facilitate material extrusion, and extend the printable time [21,23,51]. The printing speed and resolution may be further improved by selecting a suitable heating parameter.…”
Section: Performance Of the Pi/cnc Composite Aerogelsmentioning
confidence: 99%
“…The thermal imidization also induces a significant shrinkage of the printed object. Wang et al demonstrated that DIW with a rapid drying apparatus enabled 3D printing of PI from poly(amic acid) ammonium salt (PAAS) hydrogels [21]. Water-soluble PAAS inks can be prepared by mixing polyamic acids and triethylamine (TEA).…”
Section: Introductionmentioning
confidence: 99%